Improving Pumpkin Seed Processing Technology - Nazirova Raxnamoxon Muxtorovna; Umaraliyeva Maloxat (Web of Journals Publishing, 2023)
It is known that unsaturated fats are important for the normal functioning of the human body. Pumpkin seed oil is a source of unsaturated fats and has a rich amino acid content. The article shows the improvement of the technology of extracting oil from pumpkin seeds. Pumpkin oil obtained in this way has a rich lipid composition.
Keywords: pumpkin, pumpkin oil, cold pressing, chemical composition, carotenoids, pumpkin varieties, phospholipid composition.